Supply chain and local in-transit handling of ‘Jewel’ tomato from Maragusan, Davao del Norte to Baybay City, Leyte in the Philippines - Bayogan, E.V.; Secretaria, L.B.; Bello, D.D.; Urquiola, M.A.J.; Valida, A.J.; Fuentes, F.R. (CGIAR, 2023)
Tomato (Solanum lycopersicum) is a high-value crop widely grown in the Philippines. It has been reported to be second in rank after eggplant in terms of production area (Department of Agriculture, 2023). As of the second quarter of 2023, the estimated production was recorded at 70.33 thousand metric tons (PSA, 2023). The market for tomatoes comprises both fresh and processed markets. Tomatoes are well-known for their nutritional benefits, containing high levels of Vitamins A and C, and are also famous for their antioxidant properties (Srinivasan, 2010). The evaluation of tomato fruit revolves around its quality and color during harvest time. The quality of tomatoes is determined by various factors such as maturity stages, ripening, physical characteristics, and chemical properties. However, tomatoes are highly perishable. As little as 50% of annual production may reach the market, the remaining half being lost between production and consumption (Kader, 1992). Postharvest losses in the Philippines during the supply chain from Nueva Ecija to markets in Manila (such as Divisoria and Bulacan) were reported to be between 10-18% upon arrival at the market and 41% after 7 days in storage (Antolin et al., 2022). Another study showed that freshly harvested tomatoes from Bukidnon in Northern Mindanao to Manila resulted in postharvest losses of 41,125 tons, which is roughly equivalent to PHP 180 million. These losses could be minimized through the use of proper storage and packing facilities (SEAMEO SEARCA, 2022). Postharvest losses in fresh produce pose a significant challenge for the agricultural and food sectors. These losses are primarily attributed to factors such ethylene-accelerated ripening, deterioration, senescence, and biological aging (Sisler et al., 2006). Additionally, mechanical damages during transportation, such as abrasion and bruising, contribute to these losses. Addressing these challenges in postharvest handling and transportation is important to minimize losses and improve the efficiency of supply chain management. In this study, the effect of improved packing and handling methods on tomato quality compared to traditional postharvest practices was evaluated along the supply chain from Maragusan, Davao de Oro to Baybay, Leyte.